Relação entre a inteligência emocional e o rendimento escolar em crianças do 1. º Ciclo do Ensino Básico da RAM - Silva, Elisabete Porto (2021)
The growing interest in emotional intelligence has motivated, since the ‘ 90, the development of numerous studies on the topic. One of the approaches of these studies has been the relationship between emotional intelligence and academic achievement, without much agreement on the results (Angelo, 2007; Newsome et al., 2000; O’Connor & Little, 2003; Parker et al.,2004; Parker et al., 2006; Silva & Duarte, 2012) and was developed further this research. The survey was developed with a set de129 individuals of both sexes of RAM (Autonomy Region of Madeira) in order to respond to the questions: is there any relationship between IE, the IE perceived and school per formance? Does gender, age, social participation, socio-economic status of parents and school retention influence the IE and the school performance? The instruments used were: A demograph ic and educational survey where they gathered, in addition to the socio-demographic data, academ ic performance data as: retention, the notes of the Portuguese language, Mathematics, the Study of the Middle note of calibration tests: Portuguese language and Mathematics; and the Emotional Intelligence survey of Bar-On (Candeias & Rebocho, 2007, Candeias et al., 2008). The results reveal that only some aspects of IE relate to some of the variables of school performance, in particular the classifications to Portuguese and Mathematics.